Laparoscopic Varicocelectomy by Artery Preserving and Mass Ligation Technique- A Comparative Study - Islam, Sardar Rezaul; Paul, Debobrato; Sarkar, Shah Alam; Islam, Sardar Saminul; Hanif, Mohammad (British Journal of Healthcare and Medical Research, 2022)
Background- There are multiple methods of varicocele treatment. No single approach is adopted as the best therapeutic option. Laparoscopic varicocelectomy (LV) is one of them. Artery sparing laparoscopic varicocelectomy was found to have high recurrence in literature. Retroperitoneal mass ligation of testicular vein and artery was first done in original Palomo operation. Chance of missing some veins are also less if mass ligation is done in LV. Testes get blood supply from testicular artery, cremasteric artery and artery to the vas. For this reason ligation of the testicular artery in the abdomen do not cause ischemia to testes. We present our experience on comparative study between LV with mass ligation (ML) and artery preserving (AP) technique. We compared the operation time, outcome, and complication in two groups of patients. Methods-Forty-eight varicoceles, both unilateral and bilateral, were operated over a period of three years. Twenty three underwent ligation of veins alone and twenty-five underwent ligation of testicular veins and artery en-mass. They were followed up for a period of three months after surgery. We collected all data in a prospective manner. Results: The average operation time for the artery-preserved and the mass ligated group was 41±5 minutes and 27±3 minutes respectively. Average post-operative hospital stay was 46±12 hrs. and 32±7 hours respectively. There were no technical failures in either group. Complications and recurrence were less in the mass-ligation than in the artery-preserved group. On an average follow-up of 3 months all patients remained asymptomatic and had complete reduction in the size of the varicoceles. There were no incidence of testicular atrophy in either group. Conclusion: Laparoscopic varicocelectomy with mass ligation technique is safe, effective, less time consuming and easy to perform. Recurrence and post-operative complications are minimum. This should preferably be done with mass ligation with an attempt to spare lymphatics.